Effects of Long Durations of RF–Magnetron Sputtering Deposition of Hydroxyapatite on Titanium Dental Implants - Safi, Ihab Nabeel; Hussein, Basima Mohammed Ali; Aljudy, Hikmat J.; Tukmachi, Mustafa S. (European Journal of Dentistry, 2021)
Objectives Dental implant is a revolution in dentistry; some shortages are still a focus of research. This study use long duration of radiofrequency (RF)–magnetron sputtering to coat titanium (Ti) implant with hydroxyapatite (HA) to obtain a uniform, strongly adhered in a few micrometers in thickness.Materials and Methods Two types of substrates, discs and root form cylinders were prepared using a grade 1 commercially pure (CP) Ti rod. A RF–magnetron sputtering device was used to coat specimens with HA. Magnetron sputtering was set at 150 W for 22 hours at 100°C under continuous argon gas flow and substrate rotation at 10 rpm. Coat properties were evaluated via field emission scanning electron microscopy (FESEM), scanning electron microscopy–energy dispersive X-ray (EDX) analysis, atomic force microscopy, and Vickers hardness (VH). Student’s t-test was used.Results All FESEM images showed a homogeneous, continuous, and crack-free HA coat with a rough surface. EDX analysis revealed inclusion of HA particles within the substrate surface in a calcium (Ca)/phosphorus (P) ratio (16.58/11.31) close to that of HA. Elemental and EDX analyses showed Ca, Ti, P, and oxygen within Ti. The FESEM views at a cross-section of the substrate showed an average of 7 µm coat thickness. Moreover, these images revealed a dense, compact, and uniform continuous adhesion between the coat layer and the substrate. Roughness result indicated highly significant difference between uncoated Ti and HA coat (p-value < 0.05). A significant improvement in the VH value was observed when coat hardness was compared with the Ti substrate hardness (p-value < 0.05).Conclusion Prolonged magnetron sputtering successfully coat Ti dental implants with HA in micrometers thickness which is well adhered essentially in excellent osseointegration.
Keywords: dental implant; field emission scanning electron microscopy; hydroxylapatite; magnetron sputtering; titanium; Vickers hardness